Realistic evaluation of hull performance for rowing shells, canoes, and kayaks in unsteady flow - Day, A.; Campbell, I.; Clelland, D.; Doctors, L. J.; Cichowicz, J. (Journal of Sports Sciences, 2011)
In this study, we investigated the effect of hull dynamics in shallow water on the hydrodynamic performance of rowing shells as well as canoes and kayaks. An approach was developed to generate data in a towing tank using a test rig capable of reproducing realistic speed profiles. The impact of unsteady shallow-water effects on wave-making resistance was examined via experimental measurements on a benchmark hull. The data generated were used to explore the validity of a computational approach developed to predict unsteady shallow-water wave resistance. Comparison of measured and predicted results showed that the computational approach correctly predicted complex unsteady wave-resistance phenomena at low oscillation frequency and speed, but that total resistance was substantially under-predicted at moderate oscillation frequency and speed. It was postulated that this discrepancy arose from unsteady viscous effects. This was investigated via hot-film measurements for a full-scale single scull in unsteady flow in both towing-tank and field-trial conditions. Results suggested a strong link between acceleration and turbulence and demonstrated that the measured real-world viscous-flow behaviour could be successfully reproduced in the tank. Thus a suitable tank-test approach could provide a reliable guide to hull performance characterization in unsteady flow.